ChemInform Abstract: Transition‐Metal‐Free Synthesis of Unsymmetrical Diaryl Chalcogenides from Arenes and Diaryl Dichalcogenides. Issue 28 (21st June 2013) - Prasad, Ch. Durga; Balkrishna, Shah Jaimin; Kumar, Amit; Bhakuni, Bhagat Singh; Shrimali, Kaustubh; Biswas, Soumava; Kumar, Sangit
Abstract In some cases the reaction with diphenyldisulfide affords dithiolated products [cf.